Are whole-exome and whole-genome sequencing approaches cost-effective? A systematic review of the literature. (October 2018) - Schwarze, Katharina; Buchanan, James; Taylor, Jenny; Wordsworth, Sarah
Abstract Purpose We conducted a systematic literature review to summarize the current health economic evidence for whole-exome sequencing (WES) and whole-genome sequencing (WGS). Methods Relevant studies were identified in the EMBASE, MEDLINE, Cochrane Library, EconLit and University of York Centre for Reviews and Dissemination databases from January 2005 to July 2016. Publications were included in the review if they were economic evaluations, cost studies, or outcome studies. Results Thirty-six studies met our inclusion criteria. These publications investigated the use of WES and WGS in a variety of genetic conditions in clinical practice, the most common being neurological or neurodevelopmental disorders. Study sample size varied from a single child to 2, 000 patients. Cost estimates for a single test ranged from 555 to 5, 169 for WES and from 1, 906 to 24, 810 for WGS. Few cost analyses presented data transparently and many publications did not state which components were included in cost estimates. Conclusion The current health economic evidence base to support the more widespread use of WES and WGS in clinical practice is very limited. Studies that carefully evaluate the costs, effectiveness, and cost-effectiveness of these tests are urgently needed to support their translation into clinical practice.